Children's disaster experiences and psychological symptoms: An international comparison between the Chilean earthquake and tsunami and Hurricane Katrina. (July 2016) - Navarro, Javiera; Pulido, Ricardo; Berger, Christian; Arteaga, Mauricio; Osofsky, Howard J; Martinez, Monica; Osofsky, Joy D; Hansel, Tonya Cross
Improved understanding of the psychological impact on children following natural disasters is needed to assist with psychological recovery. The purpose of this exploratory study was to compare the disaster experiences and psychological symptoms of children, ages 8 to 17, following the Chilean earthquake and tsunami, and Hurricane Katrina. Over one-third of all students ( N = 827) met the symptom cut-off for mental health referral. Two one-sided test (TOST) procedures revealed similar symptom levels among the Chilean and Hurricane Katrina samples and similar numbers of reported disaster experiences. Interestingly, the Chilean earthquake and tsunami sample reported more direct disaster related losses and the Hurricane Katrina sample reported more recovery related issues. The findings suggest that even with cultural and type of disaster experience differences, children's responses to disasters are similar across cultures and that mental health services are needed to support recovery.